STUDI LITERATUR ETNOMATEMATIKA DALAM PERSPEKTIF FILSAFAT ILMU - Theresia Nata Ekwandani; Sudjarwo Sudjarwo; Muhammad Nurwahidin (Sekolah Tinggi Pariwisata Mataram, 2022)
Philosophy of science as a basic knowledge has a relationship between aspects of ontology, epistemology, and axiology. The means of scientific thinking in philosophy include language, logic, mathematics, and statistics. Mathematics as a means of scientific thinking that includes numbers, algebra, geometry, calculus, and analysis. In activities in everyday life, people are often not aware of the many mathematical concepts that are applied. Human activities that are still ongoing today give rise to a habit in society that becomes culture. The integration that bridges between culture and mathematics through learning mathematics in everyday life in a certain cultural group is called ethnomathematics. This study was a Study Literature Review (SLR) of 15 articles with the aim of describing ethnomathematics from the perspective of the philosophy. Ethnomathematics is basically a way of individuals or groups of people expressing the relationship between mathematical ideas and concepts and the culture of a particular group. Ethnomathematics is essentially the expression by individuals or groups of people of the connection between a particular group's culture and mathematical ideas and concepts. There are six basic activities related to mathematical concepts, namely counting, measuring, finding locations, designing, playing, and explaining. The role of ethnomathematics includes facilities for cultural community groups in carrying out their cultural activities; ethnomathematics becomes a forum for building national character; ethnomathematics contains mathematical ideas as the first step in contextual learning that is associated with mathematical content with the sociocultural experience of an individual.